ANALYSIS OF DIFFICULTY LEVEL AND DIFFERENT POWER OF PROBLEMS IN CLASS VIII SOCIAL STUDIES SMP NEGERI 1 KLUET UTARA - MuhasBaili; Akmaluddin; Siti Mayang Sari; Mhd. Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The research entitled "Analysis of Difficulty Level and Differentiation of Class VIII IPS Subject Questions at SMP N 1 Kluet Utara" aims to analyze the level of difficulty of the questions and the differentiating power of questions in Social Studies subject in the even semester of the 2022/2023 academic year. The research used a quantitative approach, using descriptive methods. The population in this study were all students of class VIII who took the even semester test. While the sample is class VIII-2 students consisting of 34 students. To collect data, documentation and data analysis techniques were used using the formula P=N_P/N to find the difficulty level of the questions and the formula DP = (RH-RL)/(0.5 N) to calculate discriminatory power. Based on the results of the analysis of the questions made by the social studies teacher for class VIII-2, when viewed from the level of difficulty, the item items are classified as moderate or sufficient. It can be seen that of the 40 items there are 3 (7.5%) items classified as difficult, 24 (60%) items classified as moderate and 13 (32.5%) classified as easy. Meanwhile, when viewed from the difference power of the questions, it can be categorized as sufficient (moderate). This can also be seen from the results of the analysis of 40 items, showing 10 (25%) belonging to the bad category, 17 (42.5%) and questions including the sufficient category, 12 (30%) being in the good category and only 1 (2.5%) question that belong to the very good category.